Analisis Kesulitan Belajar Siswa Dalam Memecahkan Soal Aljabar di Tingkat SMP - Ghefira Alifa Meilani; Khaira Vanaya Purwanegara; Mira Mariani; Ahmad Fu’adin (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The purpose of this analysis is to find out that students have learning difficulties and in solving algebraic arithmetic operation problems. This research analysis is included in the type of exploratory qualitative conducted in one of the junior high schools in Cimahi City. The researchers collected data using the written test technique method. In this data we collected about 35 students of class VII. The results of data analysis that has been done, we can draw the conclusion that students' difficulties in solving algebraic arithmetic problems are caused by several things, namely: (1) Lack of understanding of the concept of algebra. (2) Lack of understanding in what is instructed in the problem. (3) Errors when calculating and simplifying the answer to the problem. There are several causal factors in the analysis of this study, namely students lack understanding and understanding of the concept of algebraic arithmetic operations in solving the problems given, students do not understand what commands are given from the algebraic arithmetic operations problem and students do not know how to add up in the concept of algebra.